A review on control xanthomonas oryzae in paddy cultivation using plant extracts as alternative / Mohamad Zulfahmi Ahmad - Ahmad, Mohamad Zulfahmi (Faculty of Plantation and Agrotechnology, 2019)
The antibacterial properties from the part of plant has been found in aromatic plant and medicinal plant as alternative to control Xanthomonas oryzae in rice cultivation. The use of synthetic chemical for the first prevention to control disease caused by Xanthomonas oryzae is not an effective ways as their overuse had given harmful effect to the environment such as toxicity to living things and contamination to soil. Plant extracts have antibacterial activity and used as biological control against plant pathogen. The objective for this paper were to identify the potential of plant extracts against disease caused by Xanthomonas oryzae in paddy based on the width of inhibition zone achieved and to identify the effectiveness of different plant part extracts that produce antibacterial activity. The higher significant antibacterial activities was observed from inhibition zone (mm) in diameter. Plant extracts from Cymbopogon citratus (leaves), Terminalia chebula (fruit), and Solanum tornum swart (leaves) get the higher inhibition zone and the ranged were between 34.44 – 28.8 mm diameter to against Xanthomonas oryzae. This extraction of plant part contain important sources of secondary metabolites that can defense the plant from got the bacterial infection. This paper reviewed that all plant extract have a potential to control the disease caused by bacteria blight (Xanthomonas oryzae pv. oryzae) and bacteria leaf streak (Xanthomonas oryzae pv. oryzacola) in rice cultivation.